Comparative evaluation of MicroDTTect device and flocked swabs in the diagnosis of prosthetic and orthopaedic infections. (October 2016) - Calori, Giorgio Maria; Colombo, Massimiliano; Navone, Paola; Nobile, Marta; Auxilia, Francesco; Toscano, Marco; Drago, Lorenzo
Abstract: The evolution of new prosthetic and osteosynthetic devices has led to more surgical indications, and this is accompanied by an increased incidence of septic complications in orthopaedic and trauma surgery in the general population. The strategy for choosing surgical or therapeutic (conservative) treatment is based on the identification of the pathogen: knowledge of the aetiological agents is an essential element in the decision‐making process to ensure the most effective treatment is administered. The pathogen also needs to be considered in the challenging case of doubtful infection, where perhaps the only sign is inflammation, for a more accurate prediction of progression to either sepsis or healing. Biofilm-related infections and low-grade infections may fall into this category. Biofilm slows the metabolism of microorganisms and prolongs their survival, which renders them resistant to antibiotics. Moreover, when microorganisms are embedded in the biofilm they are poorly recognised by the immune system and the infection becomes chronic. As recently demonstrated, isolation and identification of bacteria in biofilm is difficult as the bacteria are concealed. The development of an effective means of sample collection and laboratory methods that can dislodge bacteria from prosthetic surfaces has therefore become necessary. The primary aim of the study was to evaluate the reliability of an innovative technology (MicroDTTect), specifically applied to collect and transport explanted samples (prostheses, osteosynthetic devices, biological tissues), and compare with flocked swabs. The MicroDTTect system is quick and simple to use and, most importantly, is a closed system that is totally sterile and safe for the patient being treated. It contains a specific concentration of dithiotreitol (DTT) that can dislodge bacteria from the biofilm adhering to prosthetic surfaces. The numbers of positive and negative samples were measured to compare the MicroDTTect methodology with swab collection in 30 procedures. The results showed that MicroDTTect had a higher sensitivity compared to swabs (77% and 46%, respectively), and was associated with more positive results than swabs (35% and 20%, respectively). These preliminary results show that MicroDTTect is superior to swab collection for bacterial identification in orthopaedic surgery. The early identification of microorganisms that cause sepsis may help improve treatment strategies and the efficacy of therapy, which will lead to an increased healing rate, reduced severity of sequelae and improved quality of life.